Staging memory, staging strife : empire and civil war in the Octavia - Ginsberg, Lauren (Oxford University Press, 2016)
This work offers a new reading of the Octavia as a staging ground in the memory wars surrounding Nero's fall. Through an innovative combination of cultural memory theory and intertextual analysis, Ginsberg argues that the play reimagines the imperial family as waging war on itself and its people, challenging their claim that with empire came peace